Synchronized diaphragmatic stimulation: a case report of a novel extra‐cardiac intervention for chronic heart failure - Lee R. Goldberg; Ana Jorbenadze; Tamaz Shaburishvilli; Michael J. Mirro; Marat Fudim; Michel Zuber; Simon F. Stämpfli; Felix C. Tanner; Paul Erne; John G. Cleland (ESC Heart Failure)
Abstract Synchronized diaphragmatic stimulation (SDS) is a novel extra‐cardiac device‐based therapy for symptomatic heart failure with reduced ejection fraction. SDS provides imperceptible chronic stimulation of the diaphragm through a laparoscopically implanted system consisting of an implantable pulse generator and two sensing/stimulating leads affixed to the inferior surface of the diaphragm delivering imperceptible R‐wave gaited pulses that alter intrathoracic pressure improving ventricular filling and cardiac output. We describe, in a man with a history of myocardial infarctions resulting in heart failure and persistent New York Heart Association Class III symptoms despite standard therapies, the successful implantation of SDS resulting in improved quality of life, N‐terminal pro brain natriuretic peptide, cardiac function, and exercise tolerance through 12 months of follow‐up. Randomized trials are now required to validate these findings.